Optimum Concentration of Glucose and Orange II for Growth and Decolorization of Orange II by Enterococcus faecalis ID6017 under Static Culture - V. IRENE MEITINIARTI; ENDANG S. SOETARTO; EKO SUGIHARTO; KRIS HERAWAN TIMOTIUS (Indonesian Society for microbiology, 2008)
Growth and decolorization performance of bacterial grown on azodyes-containing-medium is influenced by various concentrations of carbon sources and azodyes. The optimum level of glucose and Orange II concentration for growth and Orange II decolorization by Enterococcus faecalis ID6017 are reported in this paper. The experiments were carried out in liquid static culture as batch experiments. Glucose and Orange II concentrations used in these experiments were 0.45, 0.90, 1.80 g l-1, and 40, 80, 120 mg l-1, respectively. The specific growth rate and decolorization rate of Orange II by E. faecalis were highest on the medium which contained at least 0.90 g l-1 glucose. It is necessary to note that glucose above 0.90 g l-1 gave no significant difference. On the medium containing 0.90 g l-1 glucose and 80 mg l-1 Orange II, E. faecalis grew with the highest specific growth rate (0.28 h-1) and Orange II decolorization rate (0.47 h-1). The maximum specific growth rate of biomass (μmax) and the halfsaturation coefficient (KS) under optimal conditions were 0.25 h-1 and 1.5 g.l-1, respectively. The kinetics of decolorization indicated that the process followed first order kinetics with respect to the initial concentration of Orange II. The inhibition constant (KI) was found to be 750 mg l-1 Orange II, indicating that Orange II concentration at e” 750 mg l-1 would inhibit bacterial growth to decolorize Orange II..